The benchmarking analysis of ESG transformation models of socio-economic systems in various countries (Nexo Revista Científica, 2023)
The purpose of this work is to conduct the benchmarking analysis of ESG-transformation models of socio-economic systems in various countries, such as the Russian Federation, the United States of America, Germany and China. The work used the combination of systemic, dialectical and historical approaches that allow comparing three aspects of the sustainable development of socio-economic systems: environmental, social and economic. The dynamic analysis of the sustainable development of the countries for the period 2010-2022 was carried out according to various indicators that make up the system of ESG projections and correspond to the goals of the sustainable development. The comparative analysis of the sustainable development of the countries for 2022 was carried out according to various projections of the sustainable development. To achieve the goal the article has formed the system of measurable indicators that are used in the official statistics and reflect the economic, social and environmental aspects of the sustainable development of society. The proposed system of the indicators satisfies the principles of the comparability, necessity, sufficiency and reliability allows you to evaluate the effectiveness of ESG transformation for different countries and carry out cross-country comparisons.